ESG Resilience Under Geopolitical Turbulence : Digital Infrastructure As A Moderator of Global Risks and Local Political Networks in Indonesia - Basri, Basri; Sunaryati, Sunaryati (Universitas Muhammadiyah Surakarta, 2026)
This study examines how digital infrastructure strengthens the ESG resilience of Indonesian firms facing geopolitical risks and political network dynamics. Analyzing 89 IDX-listed companies (2016–2023) using dynamic panel regression reveals three findings. Geopolitical Risk undermines ESG performance, though state-owned enterprises show greater resilience due to resource access, remaining politically vulnerable. Political Connections have no significant effect, indicating a short-term interest focus over sustainability. Digitalization directly enhances ESG performance and moderates the negative impact of geopolitical risk by boosting transparency and signaling. Robustness checks with 2SLS confirm the results. The study highlights digital infrastructure as a vital strategic tool for mitigating geopolitical risk and promoting sustainable corporate practices.